2022
DOI: 10.3390/brainsci12020286
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Game Conditions Affect Quiet Eye Depending on the Player’s Expertise: Evidence from the Basketball Three-Point Shot

Abstract: Research on attention in sport using eye-tracking methodology has highlighted that the highest levels of expertise and performance are characterized by a specific gaze behavior consisting of a perception–action variable named quiet eye. The present study aimed to understand the role of quiet eye during the three-point shot, especially in game conditions in which even a single point may determine victory or defeat. Twenty-one basketball players (twelve competitive elites and nine semi-elites) with a high-shooti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
2
5
1
Order By: Relevance
“…Contrary to our hypothesis, the results of Experiment 2 indicated that there were no discernible disparities in quiet eye duration across the various conditions, despite the mean values aligning with our anticipated expectations. While opposing prior literature (Giancamilli et al, 2022; Vincze et al, 2022), our findings may be explained in numerous ways. For example, the final motor action (i.e., mouse click) used to indicate quiet eye may have not been reflective of the true final action (e.g., mouse movement); the representativeness of the task may be too dissimilar to the real-world environment of a CS:GO game, and/or quiet eye may not be a relevant index of optimal performance in the domain in question.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our hypothesis, the results of Experiment 2 indicated that there were no discernible disparities in quiet eye duration across the various conditions, despite the mean values aligning with our anticipated expectations. While opposing prior literature (Giancamilli et al, 2022; Vincze et al, 2022), our findings may be explained in numerous ways. For example, the final motor action (i.e., mouse click) used to indicate quiet eye may have not been reflective of the true final action (e.g., mouse movement); the representativeness of the task may be too dissimilar to the real-world environment of a CS:GO game, and/or quiet eye may not be a relevant index of optimal performance in the domain in question.…”
Section: Discussioncontrasting
confidence: 99%
“…This shorter final fixation may be a further indication of a redirection of resources away from the goal-directed system (i.e., providing less total time for the detection of task-relevant information) and consequently interrupting the timing and accuracy of the athlete's motor response (i.e., mouse click). Such reduction in quiet eye duration is a consistent finding across numerous traditional sporting domains (Giancamilli et al, 2022;Moeinirad et al, 2020;Shah et al, 2020;Vincze et al, 2022). Even for minor movements (e.g., mouse control), our findings suggest that the motor system is substantially more accurate when provided with better and more timely visual information.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As the quiet eye movement time and total fixation time become longer, the pressure sensitivity and state anxiety of athletes in the quiet eye training group were reduced, and golfers' hit rate when putting under pressure increased. This research result is consistent with the findings of Broodryk et al 34 , especially under high pressure, short quiet eye training is beneficial the attention control and accurate goalkeeping performance of rugby goalkeepers, and quiet eye during three-point shots in basketball could fulfill an online control function 35 .…”
Section: Discussionsupporting
confidence: 92%
“…Pistol expert players will first aim at the target during target shooting, whereas novice players will first aim the gun and then focus on the target ( Ripoll et al, 1985 ). Compared with novice players, expert players can aim at the hoop faster and maintain attention for a longer period of time ( Kanat & Simsek, 2021 ; Rienhoff et al, 2013 ), and the quiet eye during shooting can fulfill an online control function ( Giancamilli et al, 2022 ). There have been inconsistent conclusions about the position of the shooting aiming point ( Chen & Ren, 2006 ; Mu & Li, 2015 ).…”
Section: Introductionmentioning
confidence: 99%